Single Cell Transcriptomes of In Vitro Bradyzoite Infected Cells Reveals Toxoplasma gondii Stage Dependent Host Cell Alterations - Sugi, Tatsuki; Tomita, Tadakimi; Kidaka, Taishi; Kawai, Naoko; Hayashida, Kyoko; Weiss, Louis M.; Yamagishi, Junya (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii bradyzoites establish chronic infections within their host cells. Recent studies have demonstrated that several parasite effector proteins are translocated to host cells during the bradyzoite stage of chronic infection. To understand the interaction between host cells and bradyzoites at the transcriptomic landscape level, we utilized single-cell RNA-sequencing (scRNA-Seq) to characterize the bradyzoite-induced host cell response. Distinct gene expression profiles were observed in infected host, cells with low parasite mapped reads, and mock (non-exposed) control cells. Gene set enrichment analysis showed that c-Myc and NF-κB signaling and energy metabolic pathways were upregulated by infection. Type I and II interferon response pathways were upregulated in cells with low parasite mapped reads compared to the non-exposed host control cells, and this upregulation effect was reversed in infected cells. Differences were observed in the host cells depending on the differentiation status of the parasites, as determined by BAG1 and SAG1 expression. NF-κB, inflammatory response pathways, and IFN-γ response pathways were downregulated in host cells containing T. gondiiBAG1+/SAG1−, whereas this downregulation effect was reversed in case of T. gondiiBAG1−/SAG1+. We also identified two distinct host cell subsets that contained T. gondiiBAG1+/SAG1−, one of which displayed distinct transcriptomes with upregulated c-Myc expression. Overall, these data clearly demonstrate that host cell transcriptional alteration by bradyzoite infection is different from that of tachyzoite infection, indicating fine-tuning of the host immune response.